The relationship of teachers’ confirming behaviour towards students’ communication apprehension in Malaysian private secondary schools / Muhammad Khairulsyahmi Khamis and Noorjamaatulurul Rashdi - Khamis, Muhammad Khairulsyahmi (2017)
Teacher confirmation research has suggested that a teacher’s confirming behaviours can reduce students’ apprehension towards communicating and participating in the classroom. However, more emphasis has been given to the use of observation to measure teacher confirmation when compared to the receivers’ perceptions. The core objective of this study was to determine the relationship between teacher confirmation and communication apprehension. Four separate lessons were conducted by a total of four English language teachers, where a total of 100 Form 4 students were used as samples of the study. After the lesson, students completed a set of questionnaires, which consists of the Teacher Confirmation Scale (TCS) and Classroom Apprehension Participation Scale (CAPS), on the level of students’ apprehension in participating in classroom discussion and the frequency of a teacher exhibiting confirming behaviours in the classroom. Collectively, the results indicated a “Somewhat Confirming” level of teacher confirmation and a medium level of communication apprehension among students in the classroom. The findings also indicated a strong negative correlation between teacher confirmation and communication apprehension, which means that when the teacher confirmation level as perceived by the students is high, the communication apprehension among students will be low and vice versa. Teacher confirmation appears to be a salient behaviour to promote students’ communication and participation in the classroom.